センジョウ シイク ニ ヨル ナンキョク オキアミ Euphausia superba DANA ノ サンラン コウドウ ト ショキ ハッセイ - 菊野, 秩; キクノ, ツカサ; Kikuno, Tsukasa (1981)
P(論文) 1979-80年開洋丸第1次南極海調査航海中, 1980年1月24日, 64°45.'5S, 110°04.'0Eにおいて, KOC-Aネットの0-36m傾斜引採集により得られた南極オキアミEuphausia superba DANA成熟雌20個体を船上で飼育し, 産卵行動と初期発生を観察した。水温約0.4℃において採集後3-9日に産卵が行われ, 産卵行動を写真撮影した。産卵には約50分間を要し, 成熟雌6個体について各々の総産卵数を計数して1140-1688個の値を得た。産卵後7日目から一部の幼生の孵化がみられ, 孵化率は飼育密度により大きく変動した。その後25日間メタノウプリウス期に至る初期発育過程を観察した。 During the cruise of the Antarctic Expedition R. V. KAIYO MARU in 1979-80,the rearing of the Antarctic krill, Euphausia superba DANA, was conducted in order to observe the spawning behaviour and the early development. The krills which were collected by a 0-36m oblique tow using the KOC-A net at the position of 64°-45.5'S, 114°-04.0'E on January 24,1980 were reared at 0.4℃. The time needed for completion of spawning was about 50 minutes. Spawning behaviour was photographed and sketched. The total numbers of spawned eggs counted soon after the spawning in six females were in a range of 1140-1688. Nauplii began to hatch out after seven days of spawning. The hatchability varied with the rearing density. Twenty five nauplii developed to the metanauplius stage after 25 days of spawning. departmental bulletin paper